ANALISIS NOVEL “3726 MDPL” KARYA NURWINA SARI DENGAN PENDEKATAN OBJEKTIF - Syakira Fitri Firdaus; Indah Fadhilla (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to analyze the intrinsic elements in Nurwina Sari's novel 3726 MDPL using an objective approach. This novel depicts the story of climbing Mount Rinjani as the main setting that serves as a symbol of the main character's physical and spiritual journey in facing loss, trauma, and the process of self-healing. The background of this study is the importance of understanding the strength of the structure of literary texts independently, regardless of the author's background and reader responses. The method adopted is descriptive qualitative with reading and note-taking techniques, and focuses on intrinsic elements such as theme, character and characterization, plot, setting, point of view, and message. The research findings show that this novel uses a mixed plot, characters with deep psychological conflicts, and a strong first-person point of view. The dominant setting is the Mount Rinjani climbing area, with an atmosphere that varies from calm, thrilling, to reflective. The conclusion of this study is that the novel 3726 MDPL has a strong narrative structure that is able to arouse the reader's emotions comprehensively, and an objective approach is effectively used to reveal all of its constituent elements.